How the world really works : a scientist’s guide to our past, present and future - Smil, Vaclav, ....- (London : Penguin Books, 2022)
We have never had so much information at our fingertips and yet most of us don't know how the world really works. This book explains seven of the most fundamental realities governing our survival and prosperity. From energy and food production, through our material world and its globalization, to risks, our environment and its future, How the World Really Works offers a much-needed reality check - because before we can tackle problems effectively, we must understand the facts.
Keywords: Duurzame ontwikkeling; Toekomstvisies